(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Embedded within cultural histories, traditional oral hygiene methods have been passed down through generations, embodying a community's identity and ancestral wisdom. These methods often include the use of natural materials like chewing sticks, herbal formulations, or other locally sourced components. The cultural significance and historical roots of traditional tools contribute to the rich tapestry of oral care practices across different societies. Aim: The aim of this study was to compare the impact of indigenous and conventional oral hygiene tools on gingival parameters. Materials & Methods: The study design was in accordance with Consolidated Standards of Reporting Trials (CONSORT) guidelines for reporting clinical trials and adhered to the ethical standards of the World Medical Association's Helsinki Declaration. Selected participants were randomized into two interventional groups (Group A and Group B) using a simple random number table. Results: The findings imply that miswak may provide benefits over conventional toothbrushing in promoting oral hygiene and gingival health. The observed reductions in plaque accumulation and improvements in gingival health associated with miswak usage underscore its potential as an effective alternative or supplement to standard oral hygiene practices. To test for comparative evaluation between indigenous and conventional tooth brushing on gingival health, Kolmogorov –Smirnov and Shapiro Wilk tests were performed. Conclusion: The findings suggest that miswak may offer comparable or even superior benefits to conventional toothbrushing in promoting gingival health, highlighting its potential as an effective alternative oral hygiene tool.